17=-2(3h-4)

Simple and best practice solution for 17=-2(3h-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17=-2(3h-4) equation:


Simplifying
17 = -2(3h + -4)

Reorder the terms:
17 = -2(-4 + 3h)
17 = (-4 * -2 + 3h * -2)
17 = (8 + -6h)

Solving
17 = 8 + -6h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '6h' to each side of the equation.
17 + 6h = 8 + -6h + 6h

Combine like terms: -6h + 6h = 0
17 + 6h = 8 + 0
17 + 6h = 8

Add '-17' to each side of the equation.
17 + -17 + 6h = 8 + -17

Combine like terms: 17 + -17 = 0
0 + 6h = 8 + -17
6h = 8 + -17

Combine like terms: 8 + -17 = -9
6h = -9

Divide each side by '6'.
h = -1.5

Simplifying
h = -1.5

See similar equations:

| 8(4a+2b)= | | 5z+9=6z | | Sin(35)=4/x | | 10(s+6)=100 | | 9/c=6/10 | | 6x/16 | | 6-3n=-3 | | 9/c=6/1p | | -3a+28+5a=2a-7a | | 7x+8=6x+2 | | 3x+2x=37 | | (x+50)+3x+90=180 | | 3+3(x-6)=-24 | | 4h=-5+5h | | 6(2x+3)=18 | | 8t+4=6t | | 48-4p=4 | | 238+x=-183 | | 12-4x+11=11 | | 18=2n+8 | | (x+15)+75+x=180 | | -62/3×=-8 | | 9r=8r+7 | | x/2-3=a | | (x+60)+2x+90=180 | | 9x+6=-6+6x+24 | | 6-2/3×=-8 | | 25-5t=15 | | -6w=-10w+8 | | (y)+y-12=112 | | Cos^2*x=sin^2*x | | 4=3(2) |

Equations solver categories